Economic and environmental effects of collection and primary recycling of packaging waste from hygiene and cleaning products in Serbia - Vranjanac, Žarko Goran; Spasic, Dragan (Serbian Journal of Management, 2017)
Collection and primary recycling of packaging waste from hygiene and cleaning products occupy an important place in an integral waste management system. It is a fact that management of such waste helps reduce negative economic and environmental impact on one hand and helps bring direct and indirect benefits from collection and primary recycling of the packaging waste on the other hand. In order to obtain more comprehensive data on the economic effects of management of packaging waste from hygiene and cleaning products, this paper presents a methodology for calculating the relevant values associated with the waste. The paper also provides data on the amount, type, and market value of packaging waste from hygiene and cleaning products. Using the data on economic and environmental impact of the packaging waste from hygiene and cleaning products, as well as the data on economic benefits from this type of waste, it is possible to analyse the profitability of its collection and primary recycling in Serbia.